PENGARUH PROMOSI DAN BIAYA PENDIDIKAN TERHADAP KEPUTUSAN ORANG TUA DALAM MEMILIH SEKOLAH PENERBANGAN DIFASC JAKARTA DI SERPONG TANGERANG - Mandala Putra, Andi; Nilam Kencana, Putri (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of promotions and educational costs on parents' decisions in choosing the DIFASC Jakarta flight school. The method used is a quantitative descriptive method with an associative approach. The sampling technique used is nonprobability sampling with saturated sampling (census). Data analysis uses descriptive analysis, research instrument testing, classical assumption testing, quantitative analysis, and hypothesis testing. The results of this research are that promotion (X1) and education costs (X2) have a positive and significant effect on the decision to choose (Y) with the regression equation Y = 8.570 + 0.726X1 + 0.057X2. The coefficient of determination has a simultaneous effect of 71.5%. Partially testing the hypothesis obtained a promotion figure of tcount > ttable or (7.901 > 2.001). Thus, H01 is rejected and Ha1 is accepted, meaning that there is a significant influence between promotion (X1) on the decision to choose (Y). Education Costs (X2) is a figure of tcount > ttable or (12,021 > 2,001). So H02 is rejected and Ha2 is accepted. This means that there is an influence between the independent variable, namely the cost of education (X2) on the decision to choose (Y). Hypothesis testing obtained a value of ????calculated > ???????????????????????? or (71.420 > 3.16). Thus, H03 is rejected and Ha3 is accepted, meaning that promotion (X1) and education costs (X2) together have a positive effect on the decision to choose (Y).